Hidden Mechanisms in Educational Performance: Revealing the Role of Motivation in Transformational Leadership and School Culture - Karim, Rusli; Soelistya, Djoko; Mahjudin, Mahjudin (Newinera Publisher, 2025)
This study aims to examine the influence of transformational leadership style and school culture on educational performance through the mediation role of motivation. This study uses descriptive and verification research methods with a quantitative approach. The data collection technique in this study used a questionnaire with a measurement scale used the Likert scale. The population and sample in this study were employees of Pondok Al-Furqon Desa Srowo. The sampling technique in this study used a saturated sampling technique, totaling 102 respondents. The results of the study indicate that Transformational Leadership Style, and School culture, and Motivation have an effect on Educational performance. In addition, other results show that Transformational Leadership Style and School culture have a positive and significant effect on Motivation. The results of the motivational mediation of the relationship between Transformational Leadership Style and Educational performance, that Transformational Leadership Style on Educational performance is directly greater than Transformational Leadership Style on Educational performance through Motivation mediation, this indicates a partial mediation effect. The results of the motivational mediation of the relationship between School culture and Educational performance, that School culture on Educational performance is directly smaller than School culture Style on Educational performance through Motivation mediation, this indicates a full mediation effect. This study provides Islamic boarding school managers with important insights to optimize their organization's performance and effectiveness. Developing the communication, empathy, and motivation skills needed to improve manager performance is necessary for wise and responsive leadership.